Analisis Kinerja Karyawan Pada PT PLN (Persero) UPK Tarahan - Nurazizah, Novalina; Wahyudi, Rizqi; Nugraha, Andhyka Tyaz (Universitas Medan Area, 2023)
The purpose of this study was to determine the effect of Job Rotation, Training and Development, Career Planning, and Performance Appraisal toward the Employee Performance of PT PLN (Persero) UPK Tarahan either partially or simultaneously through the T-test and F-test. This type of research is a quantitative research. The data used in this study is primary data obtained using a data collection instrument in the form of a questionnaire that has been tested for validity and reliability using SPSS 16 software. The population in this study were all employees of PT PLN (Persero) UPK Tarahan, namely 68 employees. The sampling technique used the Slovin formula so that a sample of 59 employees was obtained. The data analysis method used Structural Equation Modeling (SEM). SmartPLS 3.2.9 is a tool used to perform analysis. The partial hypothesis testing resulted that job rotation is a variable that has no significant effect on employee performance while other variables have a positive significant effect on employee performance. Simultaneous testing shows that the independent variables together have no significant effect on the performance of PT PLN (Persero) UPK Tarahan employees because the job rotation variable has an F-square value 0.05, which is 0.00, which means the null hypothesis is rejected. The program recommendations given are job instruction exercises and coaching.